THE ROLE OF THE INDONESIAN NATIONAL ARMY (TNI) IN COUNTERING TERRORISM - Herlina Tarigan; Guntur Eko Saputro (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Terrorism that occurs both in the world and in Indonesia is a crime that cannot be classified as an ordinary crime, academically categorized as an extraordinary crime. Actions of terrorism in Indonesia can already be classified as a military threat, namely threats that use armed force, are organized and are considered to have capabilities that endanger state sovereignty. The role of The Indonesian National Army task in overcoming these acts of terrorism has not been effective. The research objective is to provide government input on the importance of The Indonesian National Army role in overcoming the threat of terrorism. Research using qualitative methods is aimed at understanding social phenomena from the perspective of the participants. The results achieved were that legally, the military could also be deployed to combat terrorism both from the aspect of domestic law and in the provisions of international law.